(untitled) (Global Journal of Science Frontier Research, 2016)
Participatory field experiment was conducted at Dimeka zuriya peasant associations of Hamer woreda of South Omo zone in the 2014 main cropping season at on farm condition under rain fed using the improved legume forage species to identify the adaptable and high biomass yielding forage species. The field experiment was laid out in a randomized complete block design (RCBD) with three replications where trial agro pastoralists farm were considered as replications. The improved legume forage species tested were Lablab purpureus, Lablab intoritum, and Vigna unguiculata. Each improved legume species was planted in a single plot area of 3 m x 4m. The average fresh biomass yield (FBY) and dry matter yield (DMY) of the tested species were 20 tone/ha, 14.84 tone/ha and 12 tone/ha and 7.2 tone /ha, 4.5 tone/ha and 6.8 tone /ha for Labalab purpureus, Lablab intoritum and Vigna unguiculata.